An efficient basic heterogeneous catalyst synthesis of magnetic mesoporous Fe@C support SrO for transesterification. (April 2020) - Li, Hui; Liu, Fengsheng; Ma, Xiaoling; Cui, Ping; Guo, Min; Li, Yan; Gao, Yan; Zhou, Shoujun; Yu, Mingzhi
Abstract: To achieve the green production of biodiesel, in this study, a novel magnetic mesoporous support (Fe@C) was obtained from MIL–Fe(100) carbonization. Strontium oxide (SrO) was then loaded on Fe@C to synthesize the sufficient, easy separable and environmentally friendly heterogeneous basic catalyst (Fe@C–Sr) for transesterification on the purpose of biodiesel production. In order to obtain the optimal synthesis method, effects of the activation temperature and SrO loading amount on catalytic activity were evaluated. In addition, Fe@C and Fe@C–Sr were characterized by means of X–ray diffraction (XRD), N2 adsorption–desorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectra (FTIR), Hammett indicator method, vibrating sample magnetometer (VSM), and X–ray photoelectron spectroscopy (XPS). To assess the catalytic behavior of Fe@C–Sr, transesterification parameters of catalyst amount, molar ratio of methanol to oil, reaction time, and reaction temperature were investigated and optimized. Meanwhile, based on the optimal transesterification parameters, the reusability and resistant ability to free fatty acid and free water were further concerned to explore the catalyst stability. Graphical abstract: Image 10686 Highlights: Pore size of MIL-Fe (100) is expanded to mesoprous size after being carbonized. SrO addition enhances the saturation magnetism of Fe@C. Fe@C-Sr is more sensitive to free fatty acid compared to free water in reaction. Fe@C is an ideal magnetic mesoporous support with paramagnetic property.